A group evidential reasoning approach for enterprise architecture framework selection. (1st October 2010) - Zandi, Faramak; Tavana, Madjid
Enterprise architecture (EA) frameworks are used to ensure interoperability of information systems and improve the effectiveness and efficiency of business organisations. Several methods have been proposed for selecting suitable frameworks. Although these methods are useful, none of them captures the uncertainties inherent in multi-attribute framework selection problems that embrace both qualitative and quantitative attributes. We propose an evidential reasoning (ER) approach to aggregate subjective and objective judgements associated with qualitative and quantitative attributes rationally and systematically. The ER approach proposed here has the following advantages over other multi-attribute decision-making (MADM) approaches used for EA framework selection: 1) the relative importance of different attributes is incorporated into the model; 2) attribute ratings are treated as assessment grades rather than precise numerical values; 3) attributes can be assessed with belief functions to capture uncertainties. A case study is provided to illustrate the implementation process of the ER approach proposed in this study.